J.R.R. Tolkien’s sub-creation theory: literary creativity as participation in the divine creation - Del Rincón Yohn, M. (Routledge, 2022)
J.R.R. Tolkien is recognized as one of the great literary creators of fantastic worlds. The English author added to his literary work a reflection on the role of the fantasy writer in his theory of sub-creation. This literary theory –exhibited mainly in his essay ‘On Fairy-Stories’ and in his letters– is based on the author's own cosmovision, clearly influenced by his Catholicism, and contemplates literary creation as an analogy of divine creation. This article deals with the Christian foundation present in the idea of participation in Creation that we find in Tolkien's theory of sub-creation. It proposes an overview of the main theological questions that support this participation, taking especially into account the contribution that John Paul II makes on this issue in his ‘Letter to Artists’. © 2021 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: artistic creation; creation; John Paul II; Literature; sub-creation; Tolkien; Scopus